ANALYSIS OF THE GAP IN THE USE OF MICROSOFT TEAMS AS AN ONLINE LEARNING TOOL TOWARDS STUDENTS' MOTIVATION IN MATHEMATICS - Paramitha, Witha; Agoestanto, Arief (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2024)
The purpose of this study is to analyze the problem of using Microsoft Teams as an online learning tool on students mathematics learning motivation. The method used in this study is qualitative descriptive. Data was collected from a questionnaire of 50 students of Junior High School 2 Semarang and the structured interview from headmaster of Junior High School 2 Semarang, mathematics teacher, and 50 students of Junior High School 2 Semarang. The results of this study showed that the problems of using Microsoft Teams as an online learning tool on students motivation to learn mathematics such as problems of student interest in learning, problems of student abilities, problems of student conditions, problems of the family environment, problems of the learning environment, problems of facilities that support learning, and problems of the school environment. Efforts made to deal with these problems include providing training to teachers on the use of Microsoft Teams, providing smartphone for students who need it, motivating students by inviting various motivators, and collaboration between teachers and parents.